2021
DOI: 10.1093/wber/lhab003
|View full text |Cite
|
Sign up to set email alerts
|

Development Research at High Geographic Resolution: An Analysis of Night-Lights, Firms, and Poverty in India Using the SHRUG Open Data Platform

Abstract: The SHRUG is an open data platform describing multidimensional socioeconomic development across 600,000 villages and towns in India. This paper presents three illustrative analyses only possible with high-resolution data. First, it confirms that nighttime lights are highly significant proxies for population, employment, per capita consumption, and electrification at very local levels. However, elasticities between night-lights and these variables are far lower in time series than in cross section, and vary wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…The between estimator R 2 values were 15 points higher (at 0.86 vs. 0.71) when using the masked VNL data products rather than their unmasked counterparts. Prior studies have shown that NTL data are more powerful cross-sectional predictors of differences in GDP (and other economic activity indicators) between areas than they are predictors of time-series changes [26,28,45]. This pattern also holds for the masked V.2 VNL data, where the R 2 values for the between estimator in the cross-section were almost 30 times as high as for the within-estimator of the time-series changes.…”
Section: Results At County and State Levelmentioning
confidence: 71%
See 2 more Smart Citations
“…The between estimator R 2 values were 15 points higher (at 0.86 vs. 0.71) when using the masked VNL data products rather than their unmasked counterparts. Prior studies have shown that NTL data are more powerful cross-sectional predictors of differences in GDP (and other economic activity indicators) between areas than they are predictors of time-series changes [26,28,45]. This pattern also holds for the masked V.2 VNL data, where the R 2 values for the between estimator in the cross-section were almost 30 times as high as for the within-estimator of the time-series changes.…”
Section: Results At County and State Levelmentioning
confidence: 71%
“…The results in Table 2 are atypical of studies that relate NTL data to GDP data. While there are some county-level results for China [25], the validation studies with GDP data as a benchmark are mostly for spatially aggregated data at the national or first subnational level, even as applied studies increasingly use NTL data locally [45]. It is therefore of interest to see how the results for estimating Equation (1) change when the GDP and NTL data are at the state-level.…”
Section: Results At County and State Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…The results in Table 1 are atypical of studies that relate NTL data to GDP data. Apart from county-level in China [25] and commune-level in Vietnam [28] validation studies are mostly for aggregated data, such as the national or first subnational level, even as applied studies use NTL data locally [45]. It is therefore of interest to see how equation (1) changes with state-level data.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, estimates of the impact of the treatment on NTL data may not be very informative about the impact of the treatment on economic activity. In particular, treatment effects may be far smaller than presumed from econometric estimates using NTL data, especially if researchers assume that cross-sectional elasticities hold in the time-series context [45].…”
Section: Discussionmentioning
confidence: 97%